PENGARUH JOB INSECURITY, BURNOUT DAN ORGANIZATONAL JUSTICE TERHADAP TURNOVER INTENTION PEGAWAI BAGIAN OPERASIONAL PADA SATUAN POLISI PAMONG PRAJA KABUPATEN ROKAN HULU - Ria Diati Oktariana (Jurnal Ilmiah Cano Ekonomos, 2021)
This study aims to determine the effect of job insecurity, burnout and organizational justice on employee employee turnover intention in the Civil Service Police Unit in Rokan Hulu Regency. The population in this study were all employees of the Civil Service Police Operational unit of Rokan Hulu Regency. The research sample used a purposive sampling technique, with a total of 79 people. The independent variables in this study were job insecurity (X1), burnout (X2), organizational justice (X3), dependent variable (Y) turnover intention. Methods of data collection using observation, documentation and questionnaires. Data analysis uses multiple linear regression. Based on partial test results it is known that job insecurity, burnout and organizational justice have a significant effect on turnover intention, where the significant value indicates that it is smaller than the significant level of 0.05. The calculation of the coefficient of determination shows that the influence of job insecurity, burnout and organizational justice together has a positive effect on turnover intention of 97.5%, while the remaining 2.5% is influenced by other variables not examined.